EXAMINING THE COLLABORATION AMONG ACTORS IN MANAGING SUSTAINABLE TOURISM: A CASE STUDY OF KASONGAN TOURISM VILLAGE (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Striking a balance between external stakeholders' interests and local communities' needs is crucial for responsible tourism development. The vital to sustaining Kasongan tourism village lies in effective collaboration among various actors, aligning their interests for mutual benefits. This research examines the collaboration among actors in managing sustainable tourism through the lens of the Strong Structuration Theory (SST). A qualitative approach involved 39 respondents by utilizing interviews, focused group discussion, and open-ended questionnaires for data collection. Thematic data analysis was conducted with the assistance of NVivo version 12 software. The findings indicate strong collaboration between village leaders and the government in Kasongan tourism village while there is a weak collaboration between the government and other internal actors (i.e., artisans, households, business owners, and showroom workers. This implies less involvement of the low-level community members on the decision making. The findings suggest policymakers should educate the local community on the importance of collaboration and involving them in decision making. To the local community members results help to identify the key actors within and outside the community and collaborate with each other to manage sustainable tourism. For academics, this study extends research on community involvement of its different actors for sustainable tourism.
Keywords: Actors; Collaboration; Local community; Sustainable tourism